Pengenalan pengolahan sampah botol plastik sebagai bahan baku energi alternatif - Yudha Adi Kusuma; Dyan Hatining Ayu Sudarni (Universitas Pendidikan Indonesia (UPI), 2022)
Plastic bottles can be useful as an alternative energy raw material. Increasing knowledge among partners can reduce the circulation of plastic waste in the environment. Community service activities are carried out through lectures, demonstrations, and group discussions. The results of the z test from community service show that the z- value (5.86) z-table (1.96) and P-value = 0.000 0.005. The results of testing for community service show that receiving H1 where there is an impact before and after community service.